1998
DOI: 10.1055/s-2007-979317
|View full text |Cite
|
Sign up to set email alerts
|

Severe Akathisia during Olanzapine Treatment of Acute Schizophrenia

Abstract: Olanzapine is a newly developed atypical neuroleptic with a marked affinity to the 5-HT2, D2 and D4 dopamine receptors. Like other atypical neuroleptics olanzapine is considered to show a reduced prevalence of extrapyramidal side effects when compared to classical neuroleptic drugs. We report on three patients with acute schizophrenia, who developed severe akathisia during treatment with olanzapine (20-25 mg/d). In two of these cases akathisia resolved after withdrawal of olanzapine and substitution by a class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In the treatment of psychotic disorders newer atypical neuroleptics cause fewer side effects especially EPS, than the traditional antipsychotics, due to their different receptor-occupancy pro®le (Chung and Chiu, 1996;Collaborative Working Group on Clinical Trial Evaluation, 1998;Jauss et al, 1998). Nevertheless EPS and, indeed, akathisia also occur with newer drugs such as olanzapine and risperidone (Avantis et al, 1997;King et al, 1995), and so doses of these drugs should also be kept as low as the symptoms allow (Jauss et al, 1998).…”
Section: Treatment With Neuroleptics and Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the treatment of psychotic disorders newer atypical neuroleptics cause fewer side effects especially EPS, than the traditional antipsychotics, due to their different receptor-occupancy pro®le (Chung and Chiu, 1996;Collaborative Working Group on Clinical Trial Evaluation, 1998;Jauss et al, 1998). Nevertheless EPS and, indeed, akathisia also occur with newer drugs such as olanzapine and risperidone (Avantis et al, 1997;King et al, 1995), and so doses of these drugs should also be kept as low as the symptoms allow (Jauss et al, 1998).…”
Section: Treatment With Neuroleptics and Antidepressantsmentioning
confidence: 99%
“…Nevertheless EPS and, indeed, akathisia also occur with newer drugs such as olanzapine and risperidone (Avantis et al, 1997;King et al, 1995), and so doses of these drugs should also be kept as low as the symptoms allow (Jauss et al, 1998). The incidence of EPS with traditional antipsychotics varies, but the better designed studies agree that EPS occur in 30±50% of patients who take conventional antipsychotics at therapeutic doses.…”
Section: Treatment With Neuroleptics and Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In clinical trials of olanzapine in patients with schizophrenia, akathisia has been reported. 1 There have been only two reports describing individual cases of olanzapine-induced akathisia, 5,6 and these also occurred in patients with schizophrenia.…”
Section: Case Reportmentioning
confidence: 99%
“…Acute akathisia is a common and extremely distressing side effect of antipsychotic treatment [Barnes and Braude, 1985;Blaisdell, 1994;Miller et al, 1997;Sachdev, 1995] and is not restricted to the use of classical neuroleptics [Barnes and McPhillips, 1998;Jauss et al, 1998;Rosebush and Mazurek, 1999]. Incidence rates are reported to vary between 25 and 75% [Braude et al, 1983;Kopala et al, 1997;Miller et al, 1998;van Putten et al, 1984].…”
Section: Introductionmentioning
confidence: 99%